Interferon beta-1b in secondary progressive MS: results from a 3-year controlled study - Panitch, Hillel; Miller, Aaron; Paty, Donald; Weinshenker, Brian (Neurology, 2004)
To evaluate the efficacy and safety of interferon beta-1b (IFNbeta-1b) in subjects with secondary progressive multiple sclerosis (SPMS). This 3-year, multicenter, double-blind, placebo-controlled, randomized trial of IFNbeta-1b included 939 subjects from the United States and Canada with SPMS and Expanded Disability Status Scale (EDSS) scores ranging from 3.0 to 6.5. Subjects were randomly assigned to receive either placebo or IFNbeta-1b (250 microg or 160 microg/m2 body surface area), administered subcutaneously every other day. The primary outcome was time to progression by > or =1.0 EDSS point (0.5 point if EDSS score was 6.0 to 6.5 at entry) confirmed at 6 months. Secondary outcomes included mean change in EDSS score from baseline, relapse-related measures, MRI activity, and a standardized neuropsychological function test. There was no significant difference in time to confirmed progression of EDSS scores between placebo-treated patients and either of the IFNbeta-1b treatment groups. However, IFNbeta-1b treatment resulted in improvement on secondary outcome measures involving clinical relapses, newly active MRI lesions, and accumulated burden of disease on T2-weighted MRI. Effects were similar for both IFNbeta-1b treatment groups. Neutralizing antibodies to IFNbeta-1b were detected in 23% of 250-microg and 32% of 160-microg/m2 recipients, but their presence did not consistently affect clinical or MRI outcomes. IFNbeta-1b was also well tolerated at both doses. Although no treatment benefit was seen on the time to confirmed progression of disability, relapse- and MRI-related outcomes showed significant benefit with both dosing regimens tested, a result consistent with the outcomes of earlier clinical trials.